Hate Speech in Cyberspace: Vulnerable Groups in the Face of Regulatory Gaps in Peru - Carlin Chiroque, Melissa Stefany; Jara Luna, Juan Carlos (Revista de Derecho, 2025)
This article addresses the analysis of hate speech in cyberspace, with emphasis on its impact on vulnerable groups in Peru and the inadequacy of the current regulatory framework to address it. Factors such as anonymity, online disinhibition and the recommendation algorithms of digital platforms have facilitated its proliferation. Although Peruvian regulations criminalize certain acts of discrimination, they do not specifically address hate speech in digital environments. The article concludes with a call to establish a clear, comprehensive legal framework aligned with international standards, including proportional sanctions, preventive strategies, digital education and protection mechanisms for affected groups.